Green competence and environmental performance: Do green empowerment and green passion matter? - Mohammed A. Al Doghan; Farhan Ali Soomro; Safia Bano; Nadia A. Abdelmegeed Abdelwahed (Sustainable Environment)
Developing effective environmental performance (EP) is a significant challenge for every organization. The present paper examines the effect of green competence building (GCB), green empowerment (GE) and green passion (GP) on EP. Besides, the paper also examines the mediating effect of GE and GP on GCB and EP. The study is quantitative, where researchers collected 298 responses from administrative and faculty staff of different public sector universities of Saudi Arabia employing a survey questionnaire. The PLS-SEM analysis exerts a positive influence of GCB on EP and GP. On the other hand, the effect of GCB on GE is not statistically significant. Moreover, the GP factor is a positive predictor of GE and EP. Finally, GE has a positive effect on EP. Concerning mediating effects, GE mediates the connection between GCB and EP. On the other hand, GP does not mediate the association between GCB and EP, and GE also does not develop the association between GP and EP. Based on the findings, the study recommends that policymakers and university authorities focus on developing an environment full of environmental awareness and skills among individuals within an organization. The study enriches and creates enthusiasm and commitment for the environment, where individuals engage in environmentally friendly behaviours and bring robust environmental sustainability. The study also recommends that organizations prioritize GCB to enhance EP and GP while nurturing a culture that inspires a passion for sustainability.